2015
DOI: 10.1371/journal.pone.0134761
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Apparent Diffusion Coefficient and Intravoxel Incoherent Motion for Differentiating among Glioblastoma, Metastasis, and Lymphoma Focusing on Diffusion-Related Parameter

Abstract: Background and PurposeBrain tumor cellularity has been assessed by using apparent diffusion coefficient (ADC). However, the ADC value might be influenced by both perfusion and true molecular diffusion, and the perfusion effect on ADC can limit the reliability of ADC in the characterization of tumor cellularity, especially, in hypervascular brain tumors. In contrast, the IVIM technique estimates parameter values for diffusion and perfusion effects separately. The purpose of our study was to compare ADC and IVIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 19 publications
1
34
0
1
Order By: Relevance
“…Our result is concordant with these prior studies . The limited value of D* was previously explained by poor reproducibility . However, Lai et al suggested that D* could be a reliable parameter for differentiating nasopharyngeal carcinoma and postchemoradiation fibrosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our result is concordant with these prior studies . The limited value of D* was previously explained by poor reproducibility . However, Lai et al suggested that D* could be a reliable parameter for differentiating nasopharyngeal carcinoma and postchemoradiation fibrosis.…”
Section: Discussionsupporting
confidence: 93%
“…Le Bihan et al were the first to describe the intravoxel incoherent motion (IVIM) modeling of DWI data and presented that it can separately account for tissue diffusion and microcapillary perfusion. It has been used in the diagnosis of several types of tumors and nodal metastasis in patients with head and neck carcinoma . The purpose of the current study was to investigate the usefulness of quantitative IVIM parameters in the preoperative diagnosis of nodal metastasis in patients with rectal carcinoma.…”
mentioning
confidence: 99%
“…The D and DDC were not correlated with any perfusion parameters derived from DSC, but the alpha value analyzed by the stretched model was moderately correlated with the DSC-rBF. The D and DDC are independent in terms of perfusion information, but the non-Gaussian effect of IVIM is somewhat related to the rBF (16,30).…”
Section: Discussionmentioning
confidence: 99%
“…The IVIM procedure concurrently determines perfusion and diffusion parameters of tumors (3,(15)(16)(17)(18)(19)(20) without the need for contrast medium (3,9). This method has major advantages because it is safe, repeatable, quantitative, and independent of arterial input function (3,16,19). Although IVIM is used to assess head and neck tumors (5,19), breast tumors, and other kinds of tumors and diseases (8,18), its characteristics and differences from other perfusion MRI techniques remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Using the acquired DWI images, ADC maps of all three planes were calculated. Additionally, the multiple b‐value sagittal rFOV DWI images were used to calculate the IVIM diffusion using the biexponential model . The IVIM‐derived parameters evaluated were true diffusion coefficient (D t ), pseudodiffusion coefficient (diffusion within the microcirculation) (D*), perfusion fraction (contribution of water moving in capillaries) (f), and ADC.…”
Section: Methodsmentioning
confidence: 99%